2017
DOI: 10.3389/fpsyg.2017.00449
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Trauma: The Effect of Early Traumatic Experiences and Adult Attachment on Parental Reflective Functioning

Abstract: There are many risk factors that make the transition to parenthood difficult, even in the best of circumstances. One such risk factor is the experience of parental childhood trauma, which has the potential to affect the parent/child relationship, both in terms of attachment style parental reflective functioning. This study aims to expand on the line of research concerned with the effects that trauma has once that child transitions into adulthood and into parenthood by looking at the role that the experience of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
1
19
1
2
Order By: Relevance
“…Our results are supported by previous studies that have highlighted that the impact of emotional abuse in childhood is harmful for development (Burns et al, 2010;Hart et al, 1997), and affecting mentalizing capacities (Bottos & Nilsen, 2014). Although neglect did not make a unique contribution in the regression, it was strongly correlated with PRF, an association supported by a previous study highlighting the negative correlation between childhood neglect and PRF (San Cristobal et al, 2017). Emotional abuse is one of the most common, yet often underreported forms of adversity (Trickett, Mennen, Kim, & Sang, 2009).…”
Section: Partsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are supported by previous studies that have highlighted that the impact of emotional abuse in childhood is harmful for development (Burns et al, 2010;Hart et al, 1997), and affecting mentalizing capacities (Bottos & Nilsen, 2014). Although neglect did not make a unique contribution in the regression, it was strongly correlated with PRF, an association supported by a previous study highlighting the negative correlation between childhood neglect and PRF (San Cristobal et al, 2017). Emotional abuse is one of the most common, yet often underreported forms of adversity (Trickett, Mennen, Kim, & Sang, 2009).…”
Section: Partsupporting
confidence: 90%
“…As such, PRF has been considered an intergenerational resilience factor. Previous studies have identified negative associations between PRF and emotional abuse (Bottos & Nilsen, 2014;Burns et al, 2010;Hart, Binggeli, & Brassard, 1997) and between PRF and neglect (San Cristobal, Santelices, & Fuenzalida, 2017), indicating that different forms of adversity might affect PRF differently (Teicher, Samson, Polcari, & McGreenery, 2006). Furthermore, a good enough attachment relationship is theorized to lead to an interpersonally transmitted knowledge, called epistemic trust.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although this study examines PRF in association with psychopathology only, the results tap into the notion of PRF as a complex and dynamic capacity at interplay with variability in context [ 113 ]. This further puts emphasis on the value of applying a multidimensional approach to the assessment of PRF, and on how the dimensions interact differently with important factors, such as the influence of partners [ 114 , 115 ] and the social environment [ 116 ], as well as the parent’s experiences with their own caregiver(s) [ 15 , 27 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated other personal outcomes. Insecurely attached new parents, for example, report greater parental strain and poorer coping [37,45] and less parental reflective functioning [46] across the transition. Moreover, women who enter parenthood seeking less spousal support or who have highly avoidant husbands tend to become more avoidant across the transition, whereas men who report providing more prenatal support to their wives become less avoidant [47].…”
Section: Personal Outcomesmentioning
confidence: 99%